Selected school solutions in the field of a healthy lifestyle among children and adolescents - Zuzanna Rykiel; Paulina Pelic; Natalia Południak; Dominik Drzewi; Natalia Szymańska; Justyna Burakowska; Daria Skrzek; Katarzyna Suchowicz; Michał Chrzanowski; Piotr Czerw; Aneta Rejman (Kazimierz Wielki University, 2021)
Introduction and aim: Lifestyle is the daily behaviors, habits and activities adopted by people. It is one of the factors that largely determines the state of human health. It is important to pay attention to what habits and activities we implement in our lives. The source of behaviors are usually attitudes and values acquired in the family and the nearest social environment. The basic categories of pro-health behaviours are related to physical health, psychosocial health, health prevention and avoiding harmful behaviours, preventing an illness and supporting recovery. Anti-health behaviors contribute to health disorders, negative impacts in emotional, physical and psychosocial sphere. The aim of the study was to present selected school solutions in the field of pro-healthy lifestyle among children and adolescents, the influence of pro-healthy lifestyle and assessment of the implementation of health education at schools. Material and method: 85 children and adolescents in the age range of 10-19+ years participated in the study. Twenty-three students in the age range of 10-12 years, 27 students in the age range of 13-16 years and 35 students in the age range of 17-19+ years were surveyed. Twenty-eight males and 57 females took the survey. Results: Respondents most often engage in physical activity 2-3 times per week. The vast majority of respondents actively participate in physical education classes at school as well as undertake extracurricular physical activity. The most popular activities are cycling and team games. The main source of knowledge about pro-healthy lifestyle among children and adolescents is the Internet and the least popular is the press. Conclusions: The majority of students know what a pro-healthy lifestyle is, while less than half of the respondents have no such knowledge. The researched gain knowledge about the way of promoting pro-healthy lifestyle by school, most often through the organization of "Health Day". The majority of children and adolescents participate in extracurricular physical activity, while the rest of the respondents do not undertake such activity.